KONSEP PENDIDIKAN INKLUSI DI SEKOLAH DASAR: SEBUAH TINJAUAN KONSEPTUAL - Elsa Viora Elsa Viora; Weni Yulastri; Putra Elgireza; Putri Nabila Rahmadina; Sunanda Zalianti (STKIP Subang, 2026)
Inclusive education is an educational system that provides equal opportunities for all children, both those with special needs and those with exceptional talents, to learn alongside their peers in the same environment. This study aims to examine in-depth the concept of inclusive education at the elementary school level, including its definition, objectives, characteristics, and implementation dynamics. The research method used was a literature review, collecting, identifying, and qualitatively analyzing various relevant literature sources, such as national and international books and scientific articles. The results indicate that inclusive education in elementary schools requires the application of innovative, creative, and flexible learning principles, integrated into the curriculum, teaching methods, and evaluation systems. The success of an inclusive education system will have positive impacts on several parties, including increasing children's self-confidence, honing teachers' pedagogical skills in diversity, and positioning parents as equal partners in the school. Collaboration between principals, teachers, and the community is a key supporting factor. However, its implementation still faces significant obstacles, such as negative paradigms from some communities, parental resistance, teachers' limited knowledge of handling children with special needs, and limited supporting facilities.